2009
DOI: 10.1098/rstb.2009.0131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on mammalian reproduction

Abstract: Heat stress can have large effects on most aspects of reproductive function in mammals. These include disruptions in spermatogenesis and oocyte development, oocyte maturation, early embryonic development, foetal and placental growth and lactation. These deleterious effects of heat stress are the result of either the hyperthermia associated with heat stress or the physiological adjustments made by the heat-stressed animal to regulate body temperature. Many effects of elevated temperature on gametes and the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
427
0
32

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 579 publications
(476 citation statements)
references
References 96 publications
17
427
0
32
Order By: Relevance
“…Other authors have reported similar declines in milk yield at low THIs or cold temperatures (Rodriquez et al, 1985;Bruegemann et al, 2012). The rate of decrease in milk yield in our study was greater at higher values of THI than at lower values, consistent with the idea that endotherms are more tolerant of low than high body temperatures (Hansen, 2009). Cows that were indoors showed an overall decrease in milk yield with increasing THI (measured from an outdoor weather station).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Other authors have reported similar declines in milk yield at low THIs or cold temperatures (Rodriquez et al, 1985;Bruegemann et al, 2012). The rate of decrease in milk yield in our study was greater at higher values of THI than at lower values, consistent with the idea that endotherms are more tolerant of low than high body temperatures (Hansen, 2009). Cows that were indoors showed an overall decrease in milk yield with increasing THI (measured from an outdoor weather station).…”
Section: Discussionsupporting
confidence: 90%
“…High temperatures are associated with a greater incidence of heat stress in livestock, which can have negative effects on milk yield (Bohmanova et al, 2007;Hammami et al, 2013), fertility (Hansen, 2009) and health , and increase the risk of mortality (Vitali et al, 2009). Heat stress occurs when animals experience conditions above their thermal comfort zone and are unable to dissipate enough heat to maintain † E-mail: davina.hill@sruc.ac.uk Animal (2015), 9:1, pp 138-149 © The Animal Consortium 2014 doi:10.1017/S1751731114002456 animal 138 thermal balance (Kadzere et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Incubation of spermatozoa at 398C for 24 h before fertilisation has been reported to decrease blastocyst developmental competence (Lechniak et al 2003), which we confirmed in the present study using spermatozoa incubated at 418C for 4 h. It is conceivable that the quality of blastocysts produced after fertilisation of oocytes with heatstressed spermatozoa is compromised because of the increased level of sperm DNA damage. Similarly, several studies have reported that mice exposed to scrotal heat stress have an increased percentage of spermatozoa with high levels of DNA damage and, as such, insemination using these spermatozoa ultimately resulted in impaired blastocyst formation (Jannes et al 1998;Paul et al 2008;2009). Further in vitro studies in cattle have confirmed these findings: Walters et al (2005aWalters et al ( , 2005b observed less blastocyst development with higher ACR after fertilisation of oocytes with semen collected from scrotalinsulated bulls.…”
Section: Discussionsupporting
confidence: 70%
“…Heat stress has long been identified as a possible cause of subfertility in farm animals, especially in hot and humid climates (for a review, see Hansen 2009). However, the molecular basis of heat stress-induced toxicity has not been entirely characterised.…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress has been recognized as a leading cause for subfertility in farm animals due to sperm damage (Hansen 2009). MAPK signal transduction, which is activated in response to several environmental stressors, promotes the inhibition of cell growth and apoptosis (Wada and Penninger 2004); specifically, MAPK signaling pathway has been shown to be involved in heatinduced sperm damage (Rahman et al 2014).…”
Section: Effect Of Heat Stress On Fertility Through Mapk Signaling Pamentioning
confidence: 99%